PERANCANGAN BOARD GAME “HAI” BERBASIS TANYA-JAWAB SEBAGAI PENGINGAT KESADARAN BERSOSIAL REMAJA - RESTU NANDA PRATAMA, Dr. M. Nasrul Kamal, M.Sn., Dini Faisal, S.Ds., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The concept of edutaiment board game based on question and answer communication, in the game there are rules that support the interaction patterns among players, that is with the activity of mutual question and answer by means of stringing words to be a question of some game cards. Board of this game will be supported by some supporting media for promotional purposes such as packaging, rulebook, sticker, totebag, t-shirt, mug, x-banner, and social media instagram. Data were collected using the 5W + 1H approach to illustrate the results of the analysis used as the basis or the foundation for the preparation of objectives and strategies in game content creation.Keywords: board game, gadget addiction phenomenon, edutaiment game, social interaction